2004
DOI: 10.1542/peds.2003-0999-l
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Steps: A Case Study of Innovation in Pediatric Practice

Abstract: Healthy Steps (HS) represents a significant innovation in the way pediatric primary care can be delivered. Based on the standards and principles of Bright Futures and the American Academy of Pediatrics Health Supervision Guidelines, HS enhances and expands traditional pediatric care by including a child development specialist (Healthy Steps specialist) as part of the pediatric practice team. Services offered by this person, typically a nurse, early childhood educator, or social worker, include more time to spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 29 publications
0
51
0
Order By: Relevance
“…The role of the PC, however, is not to enhance WCC as currently provided by the pediatrician 43 but to instead serve as the primary provider of 7 We found a significant effect of the intervention on ED utilization, with a 52% reduction in the proportion of children with ≥2 ED visits, which would represent a substantial savings in costs over a large population of children. The rate of ED utilization in our control group is similar to national data, in which 15.3% of Medicaid-insured children aged <6 years made ≥2 ED visits in the previous 12 months.…”
Section: Discussionmentioning
confidence: 80%
“…The role of the PC, however, is not to enhance WCC as currently provided by the pediatrician 43 but to instead serve as the primary provider of 7 We found a significant effect of the intervention on ED utilization, with a 52% reduction in the proportion of children with ≥2 ED visits, which would represent a substantial savings in costs over a large population of children. The rate of ED utilization in our control group is similar to national data, in which 15.3% of Medicaid-insured children aged <6 years made ≥2 ED visits in the previous 12 months.…”
Section: Discussionmentioning
confidence: 80%
“…10,30 Program costs, however, have limited its ability to be widely adopted. 31 Distinct from previous comprehensive models for redesigned WCC, the CABs had an explicit goal of decreasing reliance on physician time for routine WCC services while simultaneously providing more time for parents to discuss anticipatory guidance, psychosocial concerns, and developmental and behavioral concerns with a preventive care professional. The families served by these practices had multiple psychosocial needs often related to poverty, as well as numerous concerns regarding behavior and development.…”
Section: Model 4: Technology-based Modelmentioning
confidence: 99%
“…43 The Commonwealth Fund's Healthy Steps intervention included home visiting by masters-level healthy development specialists with significant gains in the quality of well-child care, although the multifactorial nature of this intervention made it difficult to evaluate the effectiveness of the home-visiting component. [44][45][46] A South Carolina study showed that a program that linked school-based home visitors to group well-child visits resulted in greater retention of anticipatory guidance and improved satisfaction with care. 47 These initiatives provide a glimpse into the potential of linking home visitors with the pediatric medical home.…”
Section: Benefits Of Home-visiting Programsmentioning
confidence: 99%